1983
DOI: 10.1182/blood.v62.5.1135.bloodjournal6251135
|View full text |Cite
|
Sign up to set email alerts
|

Autoplex versus proplex: a controlled, double-blind study of effectiveness in acute hemarthroses in hemophiliacs with inhibitors to factor VIII

Abstract: In view of uncontrolled observations and anecdotal reports suggesting that the activated PCC, Autoplex, was much more effective than standard (non-activated) PCC in controlling bleeding in hemophiliacs with inhibitors, a controlled double-blind study was designed to compare the effectiveness of Autoplex and Proplex. Acute hemarthrosis was chosen for study as this common but non-life-threatening lesion lends itself well to controlled study. A single dose of “unknown” product (Autoplex 75 FECU/kg; Autoplex 50 FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 0 publications
2
71
0
Order By: Relevance
“…FEIBA was found to be more effective than PCCs in a controlled comparison, with response rates of 64% and 52% respectively (Sjamsoedin et al , 1981). In a further randomized, controlled trial, Autoplex was found to be no better than a PCC (Lusher et al , 1983). Response rates with FEIBA have been reported to be as high as 80–90% (Hilgartner & Knatterud, 1983; Negrier et al , 1997).…”
Section: Products Available For the Treatment Of Bleeding In Patientsmentioning
confidence: 93%
“…FEIBA was found to be more effective than PCCs in a controlled comparison, with response rates of 64% and 52% respectively (Sjamsoedin et al , 1981). In a further randomized, controlled trial, Autoplex was found to be no better than a PCC (Lusher et al , 1983). Response rates with FEIBA have been reported to be as high as 80–90% (Hilgartner & Knatterud, 1983; Negrier et al , 1997).…”
Section: Products Available For the Treatment Of Bleeding In Patientsmentioning
confidence: 93%
“…There have also been great advances for haemophiliacs with inhibitors. The efficacy of products that bypassed the need for FVIII and FIX in intrinsic coagulation was established in the early 1980s by randomized, double-blind clinical trials [30,31]. However, efficacy of products such as FEIBA and Autoplex in controlling spontaneous bleeding was less than that obtained using FVIII or FIX concentrates in patients without inhibitors (40-60% vs. 80-90%) [15][16][17][18][19][20]30,31].…”
Section: From the 1990s Until Now: A New Golden Eramentioning
confidence: 99%
“…The efficacy of products that bypassed the need for FVIII and FIX in intrinsic coagulation was established in the early 1980s by randomized, double-blind clinical trials [30,31]. However, efficacy of products such as FEIBA and Autoplex in controlling spontaneous bleeding was less than that obtained using FVIII or FIX concentrates in patients without inhibitors (40-60% vs. 80-90%) [15][16][17][18][19][20]30,31]. In the context of this much improved but still relatively unsatisfactory background, two approaches have substantially changed the picture: the development of recombinant activated factor VII (rFVIIa) as a new bypassing product and the use of immune tolerance to eradicate the inhibitor, a treatment already pioneered in the early 1980. rFVIIa can stop 80-90% of the spontaneous haemorrhages, particularly when administered early in the home setting [32,33], and elective orthopaedic surgery can be carried out safely [34,35].…”
Section: From the 1990s Until Now: A New Golden Eramentioning
confidence: 99%
“…rescue medication) was significantly lower for the 270 lg kg )1 rFVIIa group vs. aPCC (P = 0.032), and likewise it was also lower in the 90 lg kg )1 · 3 rFVIIa group vs. aPCC, although statistical significance was not quite reached (P = 0.069). Prior to the Astermark et al [5] and Young et al [6] studies, a number of studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], most of them single-arm studies and none of them directly comparing rFVIIa and aPCC, have investigated the efficacy of these two agents.…”
Section: Introductionmentioning
confidence: 99%